Implementation of the Joyful Problem-Based Learning Model in Fostering a Sense of Responsibility and Critical Thinking Among Fifth-Grade Elementary School Students in Civic Education Classes at Bunderan Public Elementary School in Surakarta - Nafisatul Munazahro; Arief Cahyo Utomo (Journal of Educational Sciences, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model based on joyful learning in PPKn learning in elementary schools and analyze its contribution to students' attitudes of responsibility and critical reasoning skills. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of PPKn teachers, the principal, and fifth-grade students at Bunderan Public Elementary School. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing to obtain systematic and valid findings. The results showed that the implementation of PBL based on joyful learning was carried out through the stages of problem orientation, student organization, investigation, presentation of results, and evaluation. Students' critical reasoning skills also improved through activities to analyze, evaluate, and conclude problems logically. Although there were still obstacles in the form of lack of participation of some students, these obstacles could be overcome through the role of teachers as facilitators and providing learning motivation. Overall, PBL based on joyful learning is effective in improving the character of responsibility and critical thinking skills of elementary school students.